2011
DOI: 10.1007/s11701-011-0314-3
|View full text |Cite
|
Sign up to set email alerts
|

Peri-operative outcomes of patients with stage IV endometriosis undergoing robotic-assisted laparoscopic surgery

Abstract: We analyzed peri-operative outcomes of 80 patients who underwent robotic-assisted laparoscopic surgery and were diagnosed with stage IV endometriosis (revised American Society for Reproductive Medicine) between January 2007 and December 2010 at a tertiary gynecologic oncology referral center with a fellowship training program. Eligible women had a combination of one or more factors: pelvic mass, sub-acute or chronic pelvic pain, dysmenorrhea, dyspareunia, elevated serum CA-125, diagnosed with stage IV endometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
1
15
0
1
Order By: Relevance
“…Among them, 11 studies were non-comparative, i.e. included women operated with RAL only (Abo et al, 2016;Bedaiwy et al, 2013;Brudie et al, 2012;Collinet et al, 2014;Ercoli et al, 2012;Lim et al, 2011;Morelli et al, 2016;Neme et al, 2013;Nezhat et al, 2011;Pellegrino et al, 2015;Siesto et al, 2014), whereas six studies were comparative, i.e. compared two series of women operated with RAL and SL (Cassini et al, 2014;Dulemba et al, 2013;Magrina et al, 2015;Nezhat et al, 2010Nezhat et al, , 2015Nezhat and Sirota, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among them, 11 studies were non-comparative, i.e. included women operated with RAL only (Abo et al, 2016;Bedaiwy et al, 2013;Brudie et al, 2012;Collinet et al, 2014;Ercoli et al, 2012;Lim et al, 2011;Morelli et al, 2016;Neme et al, 2013;Nezhat et al, 2011;Pellegrino et al, 2015;Siesto et al, 2014), whereas six studies were comparative, i.e. compared two series of women operated with RAL and SL (Cassini et al, 2014;Dulemba et al, 2013;Magrina et al, 2015;Nezhat et al, 2010Nezhat et al, , 2015Nezhat and Sirota, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Available data from non-comparative series of women that were operated using RAL, show that this treatment of endometriosis is feasible and safe. These non-comparative studies reported a low rate of complications and a significant reduction of pain at a mean follow-up of 15 months (Abo et al, 2016;Brudie et al, 2012;Collinet et al, 2014;Ercoli et al, 2012;Morelli et al, 2016;Neme et al, 2013;Nezhat et al, 2011;Siesto et al, 2014). The surgical procedures successfully performed by RAL include radical treatment of the most severe, surgically demanding and painful (Vercellini, 1997) form of the disease, which is deeply infiltrating endometriosis involving the bowel or the urinary tract.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enfin, en 2011, Brudie et al ont publié une sé rie de 80 patientes opé ré es d'une endomé triose de stade IV par coelioscopie robotassisté e [27]. La duré e opé ratoire moyenne é tait plus courte que dans notre sé rie (115 minutes) mais les procé dures é taient moins complexes (77,6 % d'hysté rectomie, 36,3 % d'uré té rolyse, pas de shaving rectal, pas de ré section digestive, pas de cystectomie partielle, pas de ré implantation uré té ro-vé sicale) et il y a eu 5 % de laparoconversions (versus 0,6 % dans notre sé rie).…”
Section: Discussionunclassified